Space-Borne Electron Accelerator Design - Lewellen, John W.; Buechler, Cynthia E.; Carlsten, Bruce E.; Dale, Gregory E.; Holloway, Michael A.; Patrick, Douglas E.; Storms, Steven A.; Nguyen, Dinh C. (Frontiers in Astronomy and Space Sciences, 2019)
Renewed interest in active experiments with relativistic particle beams in space has led to the development of solid-state radio-frequency (RF) linear accelerators (linac) that can deliver MeV electron beams but operate with low-voltage DC power supplies. The solid-state RF amplifiers used to drive the accelerator are known as high-electron mobility transistors (HEMTs), and at C-band (5-6 GHz) are capable of generating up to 500 watts of RF power at 10% duty factor in a small package, i.e., the size of a postage stamp. In operation, the HEMTs are powered with 50V DC as their bias voltage; they thus can tap into the spacecraft batteries or electrical bus as the primary power source. In this paper we describe the initial testing of a compact space-borne RF accelerator consisting of individual C-band cavities, each independently powered by a gallium nitride (GaN) HEMT. We show preliminary test results that demonstrate the beam acceleration in a single C-band cavity powered by a single HEMT operating at 10% duty factor. An example of active beam experiments in space that could benefit from the HEMT-powered accelerators is the proposed Magnetosphere-Ionosphere Connection (CONNEX) experiment [Dors et al., 2017].